ECONOMY DE POLITICS: ANALYSIS CRITICAL ON POLICY INDONESIAN ECONOMY - Prabawanti, Banun; Cholifah, Nur (MAP Observer: Jurnal Penelitian Administrasi Publik, 2025)
This article analyzes the dynamics of political economy in Indonesia’s development from a critical perspective on implemented economic policies. The study focuses on how economic decisions are shaped by the interplay of political interests, global economic pressures, and domestic priorities. Using a qualitative approach rooted in public policy analysis, this article explores several key issues, including the role of state and non-state actors in policymaking, the impact of neo-liberalism, and Indonesia’s challenges in achieving inclusive and sustainable growth. The findings reveal that Indonesian economic policy is significantly influenced by globalization and capitalist interests, which often marginalize disadvantaged groups. Structural inequality in development benefit distribution further exacerbates socio-economic gaps. This article calls for a shift toward a people-centered and justice-oriented development paradigm. It contributes to academic discourse in development political economy while offering a foundation for more equitable and nationally driven policy reforms.